Pengembangan Media Digital untuk Peningkatan Penjualan pada Momnmebanyumas - Christian Cahyono; Julianti Kasih (Universitas Kristen Maranatha, 2026)
The development of visual-based social media has transformed digital marketing strategies for micro and small enterprises. TikTok is a potential digital promotional platform due to its short, creative videos and wide audience reach. The Momnmebanyumas baby clothing store faces limitations in promotional reach and suboptimal use of digital media. This practical work aims to explain the process of developing a TikTok account as a digital promotional medium and to analyze its impact on sales improvement. A qualitative descriptive method was applied through the analysis of TikTok content and account performance during the observation period. The results show that engaging visual content, clear product information, relevant hashtag usage, and consistent posting increase engagement, audience reach, and follower growth. These improvements align with increased sales. Therefore, TikTok is effective in enhancing brand awareness, expanding market reach, and supporting sales growth at the Momnmebanyumas baby clothing store.